Respuesta :

MsRay

Answer:

y = 3x - 2

Step-by-step explanation:

The 'rule' of a function table is the expression which you use to put in a value of 'x' to get the value of 'y'.  In this case you can look at the table and look for a pattern of 'x' and 'y' values:

       +1  +1  +1  

x = 1    2    3    4  

y = 1    4    7    10

      +3   +3   +3

So, the 'x' is increasing by 1 each time and the y is increasing by 3.  However, what is 'y' when 'x' is 0?  Subtract 1 - 0 to get x = 0 and subtract 1 - 3 to get the value of 'y' or y = 1-3 = -2.  

If we multiply x by 3 and subtract -2:  3x - 2, then we should get our value of 'y' each time:

y = 1(3) - 2 = 1

y = 2(3) -2 = 4

y = 3(3) - 2 = 7

y = 4(3) - 2 = 10